Safety Net Ontario: Ontario's outsized role in the "Global Safety Net" for climate and biodiversity - Sarah A Finkelstein; Cathal Doherty; Amanda L. Loder (Canadian Science Publishing, 2023)
Dinerstein et al. present a spatially explicit global framework for protected areas needed to reverse catastrophic biodiversity losses and stabilize climate. The Province of Ontario (Canada) stands out in this "Global Safety Net (GSN)" as a critical jurisdiction for meeting those goals, because of both the large extent of roadless lands and high carbon storage in terrestrial ecosystems. Simultaneously, pressure is increasing to develop unmanaged lands in Ontario, particularly in the Far North, for resource extraction. Here, we extract data from the GSN to identify and calculate the areal extent of target regions present in Ontario and critically review the results in terms of accuracy and implications for conservation. We show that when region-specific data are incorporated, Ontario is even more significant than what is shown in the GSN, especially in terms of carbon stocks in forested and open peatlands. Additionally, the biodiversity metrics used in the GSN only partially capture opportunities for conservation in Ontario, and the officially recognized extent of Indigenous lands vastly underestimates the role of First Nations in conservation. Despite these limitations, our analyses indicate that Ontario plays an outsized role in terms of its potential to impact the trajectories both of biodiversity and climate globally.